1973
DOI: 10.1002/macp.1973.021690120
|View full text |Cite
|
Sign up to set email alerts
|

A nuclear magnetic resonance study on the conformation and molecular interaction of polyelectrolyte model compound in alcohol/water mixtures

Abstract: The conformation and molecular interaction of polyelectrolyte model compound (2,4-dimethylglutaric acid) in alcohol/water mixtures were investigated by using high resolution NMR spectroscopy.I t is shown that the local conformation of mesa-isomer in alcohol/water mixtures slightly changes with the mole fraction of ethanol. The difference in the chemical shifts of two methylene protons and the chemical shift of carboxyl protons are comparably dependent of the mole fraction of ethanol. These results, however, do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
(1 reference statement)
1
2
0
Order By: Relevance
“…This divergence in correlated intermolecular behavior may give rise to the orders of magnitudes lower viscosity of CA compared to the sucrose. NMR studies on the viscosity of organic acids in the alcohol/water system support this hypothesis by reporting that the change in viscosity is due to the long-range interaction between the nonadjacent molecular segments . Strong long-range interactions mentioned in this study may correspond to the network-like liquid structure of the sucrose droplet.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This divergence in correlated intermolecular behavior may give rise to the orders of magnitudes lower viscosity of CA compared to the sucrose. NMR studies on the viscosity of organic acids in the alcohol/water system support this hypothesis by reporting that the change in viscosity is due to the long-range interaction between the nonadjacent molecular segments . Strong long-range interactions mentioned in this study may correspond to the network-like liquid structure of the sucrose droplet.…”
Section: Discussionsupporting
confidence: 68%
“…NMR studies on the viscosity of organic acids in the alcohol/water system support this hypothesis by reporting that the change in viscosity is due to the long-range interaction between the nonadjacent molecular segments. 70 Strong long-range interactions mentioned in this study may correspond to the network-like liquid structure of the sucrose droplet. The viscosity of OAs is analyzed and predicted using the O/C ratio or the types and the number of the functional groups of the organic molecules.…”
Section: Discussionmentioning
confidence: 64%
“…The physical properties of aqueous polyacrylic acid solutions were studied by various methods. [1][2][3][4][5][6][7] The intrinsic viscosity of polyacrylic acid in alcohol/water mixtures1 indicated that the hydrogen bond between carboxyl groups affected the conformation in alcohol/water mixtures. Miyamoto and Cantow2 investigated the effect of solvents upon the conformation of meso and racemic 2,4-dimethylglutaric acids, model compounds of polyacrylic acid, by using high-resolution 1H NMR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%